The Utilization of Information Technology-Based Media in Educational Administration Magister’s Program - Kartiwi, Asti Putri; Susantob, Kadi (EARR (Educational Administration Research and Review), 2021)
Technology will be one of the determining factors of the quality of teaching learning process in the present, especially in higher education. This research aims to describe the use of information technology-based media in the magister program of education administration, faculty of teacher and educational. The research method used is a descriptive survey. The population is 163 students of the magister program of education administration with a sample of 116 people. Based on the results of the study it is known that the description of utilization of media based on information technology in the magister program of education administration is in the category very well with indicators filled including hardware, sofware and network. Advice to lecturers who use information technology-based media in the learning process should continue to strive to develop their skills and always seek new insights on the latest information technology-based media.